Biodiversity of Cacti, Northeastern Mexico: an Insight - Perez, Gisela Muro; Rodriguez, Humberto Gonzalez; Jurado, Enrique; Salas, Jaime Sanchez (International Journal of Bio-resource and Stress Management, 2023)
Approximately 563 species, grouped in 50 genera prove a great diversity of cacti in shapes, colors of its flowers in Mexico. Mexican deserts harbor a high number of species of cacti found in groups like the barrel cactus, prickly pear and pitahayas in Durango, Zacatecas, Chihuahua, Coahuila, Nuevo Leon and Tamaulipas; great variety of large saguaros in Puebla, Queretaro, Hidalgo and San Luis Potosi. Chandeliers in Sonora and Baja California States are found. In the Mesoamerican region, out of 420 species reported, 118 have at least one use by indigenous peoples. In many regions, it plays an important social role as a source of food for humans, livestock and wildlife, construction, and fuel. At the same time, number of species are under threat due to collection pressure and ecosystem degradation